Analisis Manajemen Risiko Dalam Meningkatkan Pendapatan Usaha Pada UMKM Kerupuk Amplang Kecamatan Reteh Riau - Misna; Misna, Misna; Putra Hafiz, Ahsan; Budianto, Achyat (Program Studi Manajemen Keuangan Syariah, 2025)
This research aims to analyze the risk management carried out by Micro, Small and Medium Enterprises (MSME) operating in the shrimp amplang cracker industry in Reteh District. Prawn amplang crackers are a popular traditional food in Reteh District.The research methods used were direct interviews with the owners of MSME amplang prawn crackers, field observations, and literature study. The data collected includes nformation about the types of risks faced, steps taken to reduce risks, and the impact of these risks on the MSME of amplang shrimp crackers. The research results show that Amplang cracker MSME face various types of risks, including raw material risk, competition risk, financial risk and operational risk. To reduce the risk of raw materials, some MSME players collaborate with local fishermen to ensure a stable supply of raw materials. Competition risks are overcome by innovating products and marketing strategies. The impact of risks that are not well managed can have a negative impact on the MSME of amplang shrimp crackers, such as decreasing product quality, decreasing sales and financial instability. Therefore, effective risk management is very important for the operational continuity of the Amplang shrimp cracker MSME.